Features Of Enzymatic Hydrolysis Of Fibers Of Genetically Different Cotton Lines - Nazarov K.K., Sagdiyev X.T., Kamolova Sh. (International Journal of Advanced Science and Technology, 2020)
Thecontthe ain cphystime,founspecIt warate.Keycottostudy of biological factors affecting the process of enzymatic saccharification of celaining substrates to di- and monosaccharides is an urgent task of modern biotechnology.reas of these studies is associated with the search for enzyme preparations that are most efarrying out deep destruction of cellulose. Another thing — with the study of the influeico-chemical properties and structure of cellulose on the course of bio conversion.For ththe bio degradation processes of fibers of genetic varieties of cotton plants were studied.d that the effect of enzymes on the fibers of each variety of cotton was different. The suificity of cellulases was determined with respect to the fibers of genetically different cottons experimentally established that fibers of closely related lines undergo destruction atthe